2021
DOI: 10.3389/fcell.2021.720570
|View full text |Cite
|
Sign up to set email alerts
|

Ion Mobility Coupled to a Time-of-Flight Mass Analyzer Combined With Fragment Intensity Predictions Improves Identification of Classical Bioactive Peptides and Small Open Reading Frame-Encoded Peptides

Abstract: Bioactive peptides exhibit key roles in a wide variety of complex processes, such as regulation of body weight, learning, aging, and innate immune response. Next to the classical bioactive peptides, emerging from larger precursor proteins by specific proteolytic processing, a new class of peptides originating from small open reading frames (sORFs) have been recognized as important biological regulators. But their intrinsic properties, specific expression pattern and location on presumed non-coding regions have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 86 publications
(152 reference statements)
0
7
0
Order By: Relevance
“…With the development of high-throughput sequencing technology, growing evidence has shown that noncoding RNA (ncRNA) contains a small open reading frame (sORF), which can encode microproteins with less than 100 amino acids (AAs) [4]. Studies have shown that numerous species genomes, such as Drosophila (Drosophila melanogaster) [5][6][7], mouse (Mus musculus) [8,9], and human (Homo sapiens) [10][11][12][13][14], contain millions of sORFs. The discovery of these sORF-encoded peptides (SEPs) is an expansion of the proteome and genome.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of high-throughput sequencing technology, growing evidence has shown that noncoding RNA (ncRNA) contains a small open reading frame (sORF), which can encode microproteins with less than 100 amino acids (AAs) [4]. Studies have shown that numerous species genomes, such as Drosophila (Drosophila melanogaster) [5][6][7], mouse (Mus musculus) [8,9], and human (Homo sapiens) [10][11][12][13][14], contain millions of sORFs. The discovery of these sORF-encoded peptides (SEPs) is an expansion of the proteome and genome.…”
Section: Introductionmentioning
confidence: 99%
“…The arrival time of an ion at the end of the IM separation path increases with the ion’s mass and collisional cross section (CCS), with the gas phase used in this procedure, so that the CCS value of each ion reflects its rotationally averaged cross-sectional area. Ions with smaller CCS values traverse the IM separation path faster than those with larger CCS values, adding another separation dimension beyond mass and charge to ion identifications [ 41 ]. For example, IM techniques (e.g., differential mobility spectrometry and trapped IM spectrometry) have been employed to identify and monitor isomeric peptides and improve the signal-to-noise ratio of targeted analytes without MS 2 or MS n analyses [ 42 , 43 ].…”
Section: Peptidomics Analysis: Challenges and Advancesmentioning
confidence: 99%
“…4 In recent years, it has been repeatedly shown that extending this method by adding information from machine learning-based predictions of peptide LC-MS/MS behavior further improves peptide identification strategies. 5−7 This is especially true for more challenging proteomics workflows, such as immunopeptidomics, 8−11 proteogenomics, 12 biopeptidomics, 13 and metaproteomics. 7,14 Unfortunately, implementing these advanced methods into routine proteomics data analysis workflows has remained difficult.…”
Section: ■ Introductionmentioning
confidence: 99%
“…By including additional information, such as peptide length, charge, missed cleavages, and mass accuracy, a dynamic scoring function is generated to better separate putatively correct and incorrect identifications with machine learning . In recent years, it has been repeatedly shown that extending this method by adding information from machine learning-based predictions of peptide LC-MS/MS behavior further improves peptide identification strategies. This is especially true for more challenging proteomics workflows, such as immunopeptidomics, proteogenomics, biopeptidomics, and metaproteomics. , Unfortunately, implementing these advanced methods into routine proteomics data analysis workflows has remained difficult. Indeed, data-driven rescoring tools are often difficult to use due to complex installation procedures, specialized hardware requirements, the use of custom file formats, or even poorly documented code.…”
Section: Introductionmentioning
confidence: 99%